Not all anti‐ CD38 antibodies are created equal: The epitope of felzartamab is partially DTT ‐resistant - Anja Zeretzke; Philipp Trummer; Cora P. Habicht; Clemens Schneeweiss (Transfusion Medicine, 2026)
Abstract Objectives To evaluate anti‐CD38 antibody candidates for their ability to bind to DTT‐treated CD38 and red blood cells (RBCs). Background Dithiothreitol (DTT) treatment of RBCs is routinely used to denature CD38 and mitigate interference from anti‐CD38 antibodies, such as daratumumab and isatuximab, in immunohematology testing. However, new anti‐CD38 antibodies are in development, some of which may be directed against linear or otherwise DTT‐resistant epitopes. Methods/Materials Anti‐CD38 antibody candidates were titrated in an enzyme‐linked immunosorbent assay (ELISA) to assess their ability to bind to untreated and DTT‐treated recombinant CD38. Antibody binding was subsequently confirmed by flow cytometry of RBCs. Daratumumab and felzartamab were then tested on a panel of native and DTT‐treated RBCs in the indirect antiglobulin test (IAT). Results All antibodies except felzartamab failed to bind to DTT‐denatured CD38 in ELISA at concentrations up to 1.25 μg/mL. Flow cytometry confirmed this binding pattern. In the IAT, some DTT‐treated cells remained positive with felzartamab, despite being negative with daratumumab. Conclusion Not all epitopes of anti‐CD38 antibodies are fully DTT‐sensitive. This has important implications for handling of anti‐CD38 antibody induced interference in immunohematology, and raises the question of whether DTT is an adequate solution for interference mitigation.